The regulatory framework for the use of rubble in the infrastructure: A case study (Palestine - Gaza Strip) - Al-Mabhuh, Muhammad Ali Abd Al-Hadi; Schokry, Abed Ahmad (Journal of Architecture and environment of child, 2021)
This study aims at assessing the recycling process of the debris of the destroyed buildings caused by the Israeli aggressions on the Gaza Strip and using them in renovating the infrastructure from the viewpoint of national and international institutions. The study also aims at making a proposal that ensures reaching the best results of the recycling process. A number of interviews were made with relevant experts to reach that goal. The sample of the study consisted of 17 decision makers, specialists and experts working in the field. The researchers used the descriptive and analytical methodology to assess the recycling process of the debris left after the military aggressions on the Gaza Strip. Both methods help in studying the subject of the study as it is in reality and describe it both qualitatively and quantitatively. This approach evaluated and analyzed the subject to achieve meaningful findings that reflect on the project of recycling debris in a more influential manner in developing the infrastructure that depend on foreign funding. The study tries to find a framework for such projects that will have a positive impact on human development and community empowerment in the Gaza Strip living under successive crises and siege by the Israeli occupation. Institutions asses the recycling of debris by stating that there is no formal or legal regulatory framework governing the recycling and determine the responsibilities placed on each side. There is no control and quality body to evaluate the process and the optimal handling. Moreover, the mechanisms followed are a result of accumulated experience that has not been recorded in governmental or educational institutions. These experiences were not documented in a manner that identifies mechanisms and programs. There is no consensus on the needs and no attendance of all aspects of the work. There are no plans in full, in advance (disaster management plans prepared in advance according to the specifications and principles used in the preparation of the plans). The study recommends inserting the recycling process in the plans of disaster management in all phases of mitigation, preparedness, response, recovery and planning in the Gaza Strip. All aspects of this disaster must be included in the management of the debris at all stages, especially the recovery phase, as it facilitates the process of reconstruction. Planning should be relevant to the development of the aggression; identifying the type of buildings, and calculation of the debris that will be left after the destruction, and find a plan for its recycling to be reused in the infrastructure.